Revision of the genus Zodarion Walckenaer, 1833 (part IV). The species of Morocco (Araneae: Zodariidae) - Benhalima, Souâd; Bosmans, Robert (Zootaxa, 2020)
The following new species of Zodarion Walckenaer, 1833 are described from Morocco: Z. azrouense Bosmans & Benhalima sp. nov. (♂♀), Z. ericorum Bosmans sp. nov. (♂♀), Z. jeanclaudeledouxi Bosmans & Benhalima sp. nov. (♂), Z. maghrebense Bosmans & Benhalima sp. nov. (♂), Z. mostafai Benhalima & Bosmans sp. nov. (♂♀), Z. ogeri Bosmans & Benhalima sp. nov. (♂) and Z. wesolowskae Bosmans & Benhalima sp. nov. (♂) The following new synonym is proposed: Z. variegatum Denis, 1956 = Z. maculatum (Simon, 1870) syn. nov. The Iberian species Z. isabellinum (Simon, 1870) is reported for the first time in North Africa. New distribution data and photos of all Moroccan Zodarion species are presented.